Antimicrobial stewardship through a one health lens: observations from Washington State. Issue 3 (5th September 2016) - D'Angeli, Marisa Anne; Baker, Joe B.; Call, Douglas R.; Davis, Margaret A.; Kauber, Kelly J.; Malhotra, Uma; Matsuura, Gregory T.; Moore, Dale A.; Porter, Chris; Pottinger, Paul; Stockwell, Virginia; Wagner, Carol; et al.
Abstract : Purpose: Antibiotic resistance (AR) is a global health crisis that is attracting focused attention from healthcare, public health, governmental agencies, the public, and food producers. We describe our work in Washington State to combat resistance and promote antimicrobial stewardship from a One-Health perspective. Design/methodology/approach: In 2014, the Washington State Department of Health convened a One Health Steering Committee and two work groups to focus on antibiotic resistance, the One-Health Antimicrobial Stewardship work group and the One-Health Antimicrobial Resistance Surveillance work group. The group organized educational sessions to establish a basic understanding of epidemiological factors that contribute to resistance, including antibiotic use, transmission of resistant bacteria, and environmental contamination with resistant bacteria and antibiotic residues. Findings: We describe the varied uses of antibiotics; efforts to promote stewardship in human, and animal health, including examples from the US and Europe; economic factors that promote use of antibiotics in animal agriculture; and efforts, products and next steps of the workgroups. Originality/value: In Washington, human, animal and environmental health experts are working collaboratively to address resistance from a One Health perspective. We are establishing a multi-species resistance database that will allow tracking resistance trends in our region. Gaps include measurement of antibiotic use in humans and animals; integrated resistance surveillance information; and funding for antibiotic resistance and animal health research.